Deadly predators the big cat - Gibson, Gary; Gibson, Michael R. ([S.l.] : Starcast, 2001)
Bob Bredl takes you to see how lions and cheetahs stalk the African plains. Then even in the darkest moments of survival you will appreciate the agility of the Californian cougar as it pounces from above
Title from title screen
Executive producer, Paul Sharratr ; director of photography, Vic Martin
Host: Rob Bredl
Narrated by Michael R. Gibson
DVD Format
Keywords: Felidae